1997
DOI: 10.1021/jp971310f
|View full text |Cite
|
Sign up to set email alerts
|

Solvent and Solvent Density Effects on the Spectral Shifts and the Bandwidths of the Absorption and the Resonance Raman Spectra of Phenol Blue

Abstract: We have measured the absorption and the resonance Raman spectra of a solvatochromic dye, phenol blue, in liquid and supercritical solvents. We have found anomalous solvent dependence of the absorption bandwidth in liquid solvents: the width has apparently no correlation with the absorption peak shift. On the other hand, we have found good linear correlation between the absorption peak shift and the peak position of the resonance Raman bands (the CdN and the CdO stretching modes). The relative intensities of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
55
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 66 publications
11
55
0
Order By: Relevance
“…There are a few XRD and NMR‐ and IR/Raman‐spectroscopy‐based measurements that discuss the solvent‐dependence of molecular structure and provide direct evidence for such geometrical changes 13. 42, 43 Hybrid QM/MM approaches, which account for polarization effects of the molecules owing to surrounding homogeneous and heterogeneous media, allow us to model such environment‐dependent structural modifications in the molecular probes.…”
Section: Resultsmentioning
confidence: 99%
“…There are a few XRD and NMR‐ and IR/Raman‐spectroscopy‐based measurements that discuss the solvent‐dependence of molecular structure and provide direct evidence for such geometrical changes 13. 42, 43 Hybrid QM/MM approaches, which account for polarization effects of the molecules owing to surrounding homogeneous and heterogeneous media, allow us to model such environment‐dependent structural modifications in the molecular probes.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the absorption and vibrational spectra of push-pull molecules exhibit inhomogeneous broadening attributed to solvent-solute interactions, which are particularly strong in polar solvents. [13,14,[30][31][32] However, RREP studies by Moran and Kelley found little evidence for inhomogeneous broadening in PNA, except in the hydrogen-bonding solvent methanol. [17] Perhaps in PNA, inhomogeneous broadening is a relatively minor effect, in comparison to other push-pull chromophore systems.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, conformational broadening of the absorption lineshape for the CT transition may offer a mechanism by which to test the influence of molecular structure on the electronic and vibrational dynamics of the system. [13,14,[30][31][32] In the ground electronic state, the potential surface of PNA is flat along the NO 2 coordinate (w NO2-twist % 30-60 cm…”
mentioning
confidence: 99%
“…The high-pressure apparatus for the measurement of fluorescence in supercritical fluids is described elsewhere. [24][25][26][27][28] We used two different high pressure cells for the pressure higher or lower than 35 MPa. The cell for the lower pressure is made of titanium and has four quartz windows of larger aperture.…”
Section: Methodsmentioning
confidence: 99%